Long-Term Variation of Black Carbon Absorption Aerosol Optical Depth from AERONET Data over East Asia - Naghmeh Dehkhoda; Youngmin Noh; Sohee Joo (Remote Sensing, 2020)
Absorption aerosol optical depth induced by black carbon (AAODBC) was retrieved using the depolarization ratio and single scattering albedo provided by the Aerosol Robotic Network (AERONET) inversion products over East Asia. Our analysis considered AERONET data from six sites in East Asia that are mostly affected by anthropogenic pollution, black carbon (BC) emissions, and natural mineral dust, during the period 2001–2018. We identified a rapid reduction in total aerosol optical depth (AODT) of −0.0106 yr−1 over Beijing, whereas no considerable trend was observed at the Korean and Japanese sites. The long-term data for AAODBC showed decreasing trends at all sites. We conclude that successful emission control policies were the major underlying driver of AODT and AAODBC reductions over East Asia, particularly in China, during the study period. Values of the AAODBC/AODT ratio revealed that, although these policies were successful, the Chinese government needs to undertake stricter measures toward reducing BC emissions. We found that AAODBC follows seasonal trends, peaking in the colder months. This suggests that in East Asia, particularly in China, domestic coal burning is still of concern.